2014
DOI: 10.1016/j.yjmcc.2014.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Selective inhibition of class I but not class IIb histone deacetylases exerts cardiac protection from ischemia reperfusion

Abstract: While inhibition of class I/IIb histone deacetylases (HDACs) protects the mammalian heart from ischemia reperfusion (IR) injury, class selective effects remain unexamined. We hypothesized that selective inhibition of class I HDACs would preserve left ventricular contractile function following IR in isolated hearts. Male Sprague Dawley rats (n=6 per group) were injected with vehicle (dimethylsulfoxide, 0.63 mg/kg), the class I/IIb HDAC inhibitor trichostatin A (1 mg/kg), the class I HDAC inhibitor entinostat (M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
62
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 79 publications
(64 citation statements)
references
References 39 publications
1
62
1
Order By: Relevance
“…Although PCI and angioplasty limit ischemic injury, reperfusion itself injures the heart by increasing ROS. We and others have shown that HDAC inhibition preceding ischemia reperfusion (I/R) injury in the heart can preserve left ventricular function and myocardial survival [2931]. Importantly, we demonstrated that the selective inhibition of class I HDACs was more effective than pan-HDAC inhibition in preserving myocardial viability and function in the setting of I/R injury.…”
Section: Introductionmentioning
confidence: 65%
“…Although PCI and angioplasty limit ischemic injury, reperfusion itself injures the heart by increasing ROS. We and others have shown that HDAC inhibition preceding ischemia reperfusion (I/R) injury in the heart can preserve left ventricular function and myocardial survival [2931]. Importantly, we demonstrated that the selective inhibition of class I HDACs was more effective than pan-HDAC inhibition in preserving myocardial viability and function in the setting of I/R injury.…”
Section: Introductionmentioning
confidence: 65%
“…More than one study has demonstrated a significant decrease in infarct size and myocardial cell death with class I/IIb HDAC inhibitor treatment (18,60). We recently demonstrated that class I HDAC inhibition conferred protective benefits to the ischemic reperfused heart and that inhibition of HDAC6, a class IIb HDAC, provided no beneficial effects (3).…”
Section: Discussionmentioning
confidence: 99%
“…As described previously 7 , this pressure trace can be used to calculate many of the parameters of ventricular function. These calculations can be made in the baseline phase as well as the reperfusion phase, averaged over multiple traces within each group, and compared in order to determine whether the pharmacological intervention resulted in cardiac preconditioning, as we have done previously 9 . One such parameter is the developed pressure, calculated as the difference between the systolic pressure and the end diastolic pressure.…”
Section: Representative Resultsmentioning
confidence: 99%
“…The isolated perfused rat heart can be successfully used to study the effect of pharmacological intervention on cardiac preconditioning in ischemia reperfusion injury 9 . However, there are some essential steps to the procedure that must be standardized in order to ensure reproducible results.…”
Section: Discussionmentioning
confidence: 99%